2002
DOI: 10.1177/152660280200900308
|View full text |Cite
|
Sign up to set email alerts
|

Single-Center Experience with Carotid Stent Restenosis

Abstract: Carotid stent restenosis, which occurs rarely after 1 year, can be treated safely by further percutaneous interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…10,16,17,[23][24][25][26][27]29,31,35,37,39,42 Twenty-five studies used a lower restenosis threshold Ն50% to 70%, 10 -34 whereas 16 studies used a lower threshold Ͼ70% to 80% to define a restenosis. 10,11,14,15,17,19,21,[35][36][37][38][39][40][41][42][43] In Figure 1, the proportion of patients/arteries in whom/ which restenosis developed is plotted against the average follow-up time. In both groups, the data were very heterogeneous ( 2 ϭ83, dfϭ24 in the restenosis group Ն50% to 70%, PϽ0.01; and 2 ϭ39, dfϭ15 in the restenosis group Ͼ70% to 80%, PϽ0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,16,17,[23][24][25][26][27]29,31,35,37,39,42 Twenty-five studies used a lower restenosis threshold Ն50% to 70%, 10 -34 whereas 16 studies used a lower threshold Ͼ70% to 80% to define a restenosis. 10,11,14,15,17,19,21,[35][36][37][38][39][40][41][42][43] In Figure 1, the proportion of patients/arteries in whom/ which restenosis developed is plotted against the average follow-up time. In both groups, the data were very heterogeneous ( 2 ϭ83, dfϭ24 in the restenosis group Ն50% to 70%, PϽ0.01; and 2 ϭ39, dfϭ15 in the restenosis group Ͼ70% to 80%, PϽ0.01).…”
Section: Resultsmentioning
confidence: 99%
“…10,11,[15][16][17]19,21,39,40,42,43 In both groups, Ϸ46% of all restenoses occurred within the first 6 months, Ϸ25% within 6 to 12 months, and 29% beyond the first year.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic layer of stent grafts is thought to act as a mechanical barrier allowing only minimal intimal hyperplasia. End-stent stenosis is more common with covered stents compared with conventional stents 16 and it has been suggested that it primarily occurs adjacent to a bend or kink 17 .…”
Section: Casementioning
confidence: 99%
“…In-stent restenosis (ISR) is a recognized complication of CAS, with severe restenosis (>70%) occurring in 3–5% of patients. 1 2 3 4 5 Restenosis after CAS is often asymptomatic, but is not always benign and may progress to asymptomatic occlusion or present with ischemic symptoms or stroke. 1 2 3 4 5 While the scope of future applications for CAS will depend on the results of pivotal clinical trials, there is no argument that CAS will continue to have a role in many patients, and that physicians need to understand the best management and treatment strategies for patients with severe in-stent restenosis.…”
mentioning
confidence: 99%